2019
DOI: 10.1007/s00464-019-06747-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results after elective laparoscopic surgery for colorectal cancer in octogenarians

Abstract: The aim of this study was to investigate the short and long term outcomes after elective laparoscopic surgery for colorectal cancer patients over 80 years of age. Methods: This was a retrospective study of all patients of 80 and above, who underwent elective colorectal resection, between January 2007 and January 2016. Data were analysed from a prospectively collected cancer database and cross checked with patient records. Determinants of survival were analysed using log rank test and Kaplan-Meier curves. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(20 reference statements)
0
5
0
1
Order By: Relevance
“…Laparoscopic colorectal surgery has been shown to be associated with superior perioperative outcomes to open surgery [ 9 ]. Standardization of surgical procedures and advances in surgical instruments have steadily expanded the indications for laparoscopic colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic colorectal surgery has been shown to be associated with superior perioperative outcomes to open surgery [ 9 ]. Standardization of surgical procedures and advances in surgical instruments have steadily expanded the indications for laparoscopic colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Considerando que los casos con hallazgos significativos fueron frecuentes en ambos grupos y que los pacientes octogenarios tuvieron un buen estado clínico y escasas complicaciones, nuestros datos son coherentes con publicaciones que hacen referencia a los buenos resultados que podría tener una eventual cirugía mínimamente invasiva en este grupo, no excluyéndolos únicamente por la edad como candidatos al tratamiento definitivo de su enfermedad [20][21][22] .…”
Section: Discussionunclassified
“…1,32,33 Given that colorectal cancer is the second most frequent type of cancer and that the majority of patients are older than 70-35% are older than 80-minimally invasive techniques are of particular interest in this population. 34 One of the controversial issues is the impact of conversion to open surgery on postoperative morbidity and long-term oncologic outcomes. Some authors have reported a negative impact of conversion on overall and disease-free survival while others have found no such differences.…”
Section: Discussionmentioning
confidence: 99%
“…Given that colorectal cancer is the second most frequent type of cancer and that the majority of patients are older than 70—35% are older than 80—minimally invasive techniques are of particular interest in this population 34…”
Section: Discussionmentioning
confidence: 99%